1996
DOI: 10.1097/00007890-199602270-00009
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Soluble Hla Alloantigens and Anti-Hla Antibodies Identifies Heart Allograft Recipients at Risk of Transplant-Associated Coronary Artery Disease1

Abstract: The development of accelerated transplant-related coronary artery disease (T-CAD) is the major obstacle to long-term survival of cardiac allografts. We have investigated the role of various demographic and immunologic parameters as prognostic indicators of T-CAD in a population of 274 heart allograft recipients. Our data demonstrate that patients who experience more than 1 episode of acute rejection per year and/or develop antidonor HLA antibodies are at increased risk of developing T-CAD. Using HLA-A2 as a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(56 citation statements)
references
References 28 publications
3
52
1
Order By: Relevance
“…In heart, the role of anti-HLA antibodies in acceleration of cardiac allograft vasculopathy has emerged (19,20), pointing towards the importance of antibody-mediated injury as a major culprit in many longterm failing organs including hearts, but also other solid organ transplants such as lungs, small bowel, composite tissue transplants, and kidney allografts (15,(21)(22)(23). The latter has recently been supported by the demonstration of a new rejection entity called antibody-mediated vascular rejection, characterized by circulating allo anti-HLA antibodies inducing intimal arteritis and microcirculation inflammation followed by accelerating allograft arteriosclerosis and long-term allograft failure (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In heart, the role of anti-HLA antibodies in acceleration of cardiac allograft vasculopathy has emerged (19,20), pointing towards the importance of antibody-mediated injury as a major culprit in many longterm failing organs including hearts, but also other solid organ transplants such as lungs, small bowel, composite tissue transplants, and kidney allografts (15,(21)(22)(23). The latter has recently been supported by the demonstration of a new rejection entity called antibody-mediated vascular rejection, characterized by circulating allo anti-HLA antibodies inducing intimal arteritis and microcirculation inflammation followed by accelerating allograft arteriosclerosis and long-term allograft failure (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, antigenspecific B cells may drive the indirect T-cell activation pathway by acting as potent antigen-presenting cells of soluble allo-HLA-DR peptides to self-CD4 T cells. 31,32 Therefore, prominent anti-HLA antibody production in a given transplantation recipient may correlate with a high risk for transplantation-related vasculopathy by both reflecting an activated indirect T-cell recognition pathway and an efficient alloantigen-presentation arm of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant arteriosclerosis is characterized by the proliferation of intimal smooth muscle cells (SMC) 3 and endothelial cells (EC) in the walls of the arteries of the transplanted organ resulting in occlusion of the vessels and fibrosis of the graft. Anti-HLA Abs have long been implicated in the process of chronic rejection, as several studies have shown that patients developing anti-donor HLA Abs following transplantation are at increased risk of developing chronic rejection and graft loss (3)(4)(5)(6)(7)(8)(9)(10). A consistent finding in graft arteriosclerotic lesions is Ig deposits in affected vessel walls and within the media (2,11,12).…”
mentioning
confidence: 99%